To solve the equation \(-4(3x + 10) - 2 = 54\), we can start by simplifying the left side of the equation.
- Distribute the \(-4\) to both terms inside the parentheses:
\[ -4 \cdot 3x - 4 \cdot 10 - 2 = -12x - 40 - 2 \]
- Combine the constants \(-40\) and \(-2\):
\[ -12x - 42 = 54 \]
- Next, add \(42\) to both sides of the equation to isolate the term with \(x\):
\[ -12x - 42 + 42 = 54 + 42 \]
This simplifies to:
\[ -12x = 96 \]
- Now, divide both sides by \(-12\) to solve for \(x\):
\[ x = \frac{96}{-12} = -8 \]
Thus, the solution is:
\[ x = -8 \]